Enhanced Value Stream Mapping for Improving Turnaround Process Efficiency in Oil and Gas Industry - Shou, Wenchi (Curtin University, 2018)
Turnaround maintenance (TAM) is one of the most important maintenance strategies to minimise the risk of production losses. Managing these TAM projects is challenging as for its complexity due to the involvement of massive man powers and financial resources. The aim of this research is to develop an enhanced-Value Stream Mapping (enhanced-VSM) framework to effectively improve TAM efficiency. Four theoretical enhancements are made to the conventional VSM method and validation results show the successful implementation.